Influence of Perceived Height, Masculinity, and Age on Each Other and on Perceptions of Dominance in Male Faces. (November 2015) - Batres, Carlota; Re, Daniel E.; Perrett, David I.
Several studies have examined the individual effects of facial cues to height, masculinity, and age on interpersonal interactions and partner preferences. We know much less about the influence of these traits on each other. We, therefore, examined how facial cues to height, masculinity, and age influence perceptions of each other and found significant overlap. This suggests that studies investigating the effects of one of these traits in isolation may need to account for the influence of the other two traits. Additionally, there is inconsistent evidence on how each of these three facial traits affects dominance. We, therefore, investigated how varying such traits influences perceptions of dominance in male faces. We found that increases in perceived height, masculinity, and age (up to 35 years) all increased facial dominance. Our results may reflect perceptual generalizations from sex differences as men are on average taller, more dominant, and age faster than women. Furthermore, we found that the influences of height and age on perceptions of dominance are mediated by masculinity. These results give us a better understanding of the facial characteristics that convey the appearance of dominance, a trait that is linked to a wealth of real-world outcomes.